AB0445 Therapeutic maintenance of abatacept in rheumatoid arthritis: results of the ric-aba study (517 PATIENTS). (12th June 2018) - Salmon, J.H.; Letarouilly, J.G.; Coquerelle, P.; Goeb, V.; Guyot, M.H.; Houvenagel, E.; Lecuyer, N.; Le Dantec, L.; Marguerie, L.; Morel, G.; Baudens, G.; Solau, E.; et al.
Abstract : Objectives: Study the therapeutic maintenance, associated factor with maintenance at 12 months and reasons for abatacept (ABA) stop in daily practice. Methods: Retrospective multicentric study, from the RIC Nord de France network, of patients treated for rheumatoid arthritis who received at least one ABA treatment between January 2008 and July 2016. We studied the therapeutic maintenance at 12 months, according to the number of previous bDMARDs and according to the date of initiation (group 1: from 2008 until 31/07/2010 (ABA authorised in anti-TNFfailure) and group 2 from 01/08/2010 (ABA authorised in the first line)). Therapeutic maintenance was evaluated using the Kaplan-Meier method. Results: Of the 517 patients (74% women) who were included, the mean age was 61.4±13.3 years. There were 76% positive anti-CCP. ABA was used as monotherapy in 176 patients (34%) and 22% of patients were naïve to bDMARDs. The mean DAS 28-VS at initiation of ABA was 4.7±1.3. Therapeutic maintenance at 12 months was 68%. Among the 166 patients (32%) stopped ABA, the reason for discontinuation was primary ineffectiveness (n=54, 32.5%), loss of efficacy (n=40, 24%), adverse events (n=43, 26%) and other (n=29, 17.5%). On multivariate analysis CRP <10 mg/L was associated with better maintenance at 12 months. No significant difference in therapeutic maintenance was found at 12 months according to the date of initiation and according to the number of previous bDMARDs. Conclusions: Therapeutic maintenance at 12 months was 68%, this rate is similar to Pan-European Registry. The rate of CRP at initiation seems to have an impact on the maintenance of ABA at 12 months. Reference: [1] Gottenberg JE, Courvoisier DS, Hernandez MV, Iannone F, Lie E, Canhão H, et al. Brief Report: Association of Rheumatoid Factor and Anti-Citrullinated Protein Antibody Positivity With Better Effectiveness of Abatacept: Results From the Pan-European Registry Analysis. Arthritis Rheumatol2016Jun;68(6):1346–52. doi:10.1002/art.39595 Disclosure of Interest: None declared